Description Electronic Dictionary in Kurdish Language - Iman Askandar Jawhar; Media Murad Muhammadamin (Zanco Journal of Humanity Sciences)
This research is an attempt to reveal information about dictionary, how dictionary first emerged in the world and among the Kurdish and who created the first dictionaries. Every language a dictionary in order to survive.